Excitações em cristais fotônicos unidimensionais - Araújo, Carlos Alexandre Amaral (2012)
In this work, we present a theoretical study of the propagation of electromagnetic waves in multilayer structures called Photonic Crystals. For this purpose, we investigate the phonon-polariton band gaps in periodic and quasi-periodic (Fibonacci-type) multilayers made up of both positive and negative refractive index materials in the terahertz (THz) region. The behavior of the polaritonic band gaps as a function of the multilayer period is investigated systematically. We use a theoretical model based on the formalism of transfer matrix in order to simplify the algebra involved in obtaining the dispersion relation of phonon-polaritons (bulk and surface modes). We also present a quantitative analysis of the results, pointing out the distribution of the allowed polaritonic bandwidths for high Fibonacci generations, which gives good insight about their localization and power laws. We calculate the emittance spectrum of the electromagnetic radiation, in THZ frequency, normally and obliquely incident (s and p polarized modes) on a one-dimensional multilayer structure composed of positive and negative refractive index materials organized periodically and quasi-periodically. We model the negative refractive index material by a effective medium whose electric permittivity is characterized by a phonon-polariton frequency dependent dielectric function, while for the magnetic permeability we have a Drude like frequency-dependent function. Similarity to the one-dimensional photonic crystal, this layered effective medium, called polaritonic Crystals, allow us the control of the electromagnetic propagation, generating regions named polaritonic bandgap. The emittance spectra are determined by means of a well known theoretical model based on Kirchoff s second law, together with a transfer matrix formalism. Our results shows that the omnidirectional band gaps will appear in the THz regime, in a well defined interval, that are independent of polarization in periodic case as well as in quasiperiodic case